Evaluation of Seed Fertility in Relation to Diameter Classes of Diploknema butyracea (Roxb.) H. J. Lam - Bahar, Nawa (Indian Forester, 2017)
Diploknema butyracea is a fast growing and lesser-known species. The trees of this species were grouped into different diameter classes for assessment of seed germination and seedling viour. It is investigated from the results that there was no definite relationship between size of tree and seed fertility in this species.